2019
DOI: 10.3389/fmats.2019.00070
|View full text |Cite
|
Sign up to set email alerts
|

Improving Hydrogen Sensing Performance of TiO2 Nanotube Arrays by ZnO Modification

Abstract: In this work, anodization was utilized to synthesize highly ordered TiO 2 nanotube arrays, and ZnO was successfully decorated onto the surface of as-prepared TiO 2 nanotubes via a facile impregnation method. The gas sensing performance of a TiO 2 @ZnO composite was systematically studied. At a working temperature of 300 • C, the response of TiO 2 @ZnO to 100 ppm H 2 was ∼340, 2.7 times larger than that of pristine TiO 2 . A power-law relationship between the response and H 2 concentration was observed. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Each oxygen vacancy associated with two extra electrons is likely transferred to the vacant 3d orbitals of nearby Ti 5c ions when V O states occur on the surface of TiO 2 , creating two Ti 3+ sites. 39,46 Thereby, analysis of the XPS results for the prepared nanocomposites directly reveals the presence of strong surface interaction between TiO 2 and ZnO in TiO 2 /ZnO nanocomposites.…”
Section: Chemical Composition Analysismentioning
confidence: 97%
“…Each oxygen vacancy associated with two extra electrons is likely transferred to the vacant 3d orbitals of nearby Ti 5c ions when V O states occur on the surface of TiO 2 , creating two Ti 3+ sites. 39,46 Thereby, analysis of the XPS results for the prepared nanocomposites directly reveals the presence of strong surface interaction between TiO 2 and ZnO in TiO 2 /ZnO nanocomposites.…”
Section: Chemical Composition Analysismentioning
confidence: 97%
“…However, hydrogen is extremely flammable with a lower explosive limit of 4% in air. Hydrogen poses a threat to major hazards by quick spreading of fire due to its low minimum ignition energy (0.017 mJ) and high heat of combustion (142 kJ/g). , Therefore, the need for accurate detection of hydrogen has become more important than ever before in various stages of energy generation, transportation, and usage.…”
Section: Hydrogen Sensors Based On Mo Heterostructuresmentioning
confidence: 99%
“…Hydrogen poses a threat to major hazards by quick spreading of fire due to its low minimum ignition energy (0.017 mJ) and high heat of combustion (142 kJ/g). 117,221 Therefore, the need for accurate detection of hydrogen has become more important than ever before in various stages of energy generation, transportation, and usage. The real challenge lies in the detection of hydrogen at room temperature due to the small mass of H 2 molecules and weak adsorption 222 to the sensor surface.…”
Section: Hydrogen Sensors Based On Mo Heterostructuresmentioning
confidence: 99%
“…On the other hand, the heterojunctions are often used to improve the gas sensing performance of resistive MOS gas sensors at room temperature. ,, By utilizing this approach, several reports about TiO 2 -based materials with heterojunctions have been published to enhance the hydrogen sensing performance, such as SnO 2 /TiO 2 , NiO/TiO 2 , ZnO/TiO 2 , , WO 3 /TiO 2 , , and MoO 3 /TiO 2 . , In particular, N.E. Boboriko et al have demonstrated that the MoO 3 /TiO 2 composites can exhibit excellent hydrogen gas sensing performance at 275 °C and show that the MoO 3 can be considered as a potential substitution for noble metal additives in MOS because it can maintain high catalytic and selectivity to hydrogen gas in the nanocomposites. , Unfortunately, the prepared MoO 3 /TiO 2 composite still has a high operating temperature (275 °C), which is not conducive to the practical application.…”
Section: Introductionmentioning
confidence: 99%